2016
DOI: 10.1097/meg.0000000000000661
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and two types of presarcopenia in Japanese patients with chronic liver disease

Abstract: Evaluation of handgrip strength and psoas index is an easy and effective method for the detection of sarcopenia and presarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 25 publications
6
57
2
2
Order By: Relevance
“…As noted in a previous report, the present results noted gender differences in regard to the test results. We found that a finger‐circle test result in male patients other than Bigger (Just‐fits and Smaller) predicted a decline in muscle area of L3 to PI 5.25 cm 2 /m 2 , which was approximately mean minus 1 SD (5.37 cm 2 /m 2 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As noted in a previous report, the present results noted gender differences in regard to the test results. We found that a finger‐circle test result in male patients other than Bigger (Just‐fits and Smaller) predicted a decline in muscle area of L3 to PI 5.25 cm 2 /m 2 , which was approximately mean minus 1 SD (5.37 cm 2 /m 2 ).…”
Section: Discussionsupporting
confidence: 87%
“…However, it is important to keep in mind that there are discrepancies between actual clinical practice and reported guidelines. There might be gender differences concerning to progressions of MA and MSD . Moreover, although there was no significance in increasing the percentage of sarcopenia in each stage of CLD in the present cohort ( n = 358; CH vs. LC CP‐A, vs. LC CP‐B/C = 5.8% vs. 8.3% vs. 15.4%; P = 0.110), progression of CLD stage is an important risk factor for existence of muscle abnormality .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…European Working Group on Sarcopenia in Older People, AWGS, and JSH have defined sarcopenia as MVL coexisting with muscle strength decline. In patients with CLD, sarcopenia, MVL, and muscle strength decline are not rare, even in an early stage . In addition, MVL has recently been reported as a prognostic factor for survival in HCC patients treated with liver transplantation, surgical resection, or sorafenib, although few reports have elucidated the relationship between muscle function and prognosis of HCC patients following surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prevalence of sarcopenia in previous studies may have been underestimated. Hiraoka et al . reported that the prevalence of sarcopenia in patients with chronic hepatitis and liver cirrhosis was 3.9–16.7% when sarcopenia was defined based on the psoas muscle index at the L3 level on CT and based on declined grip strength.…”
Section: Discussionmentioning
confidence: 99%